Tag Archives: Sylow’s theorems

otro lema estratégico

La siguiente lámina establece un lema vital para una demostración “más contemporánea” del Teorema de Sylow 1.


Leave a comment

Filed under algebra, cucei math, group theory, what is math

a poem, a strategic lemma


\cdot  p\in{\Bbb{P}}

\cdot |G|=p^mr , p\nmid r

\cdot \forall H<G

\cdot \forall Q\in {\rm p\!-\!SS}_G


\bullet \exists g\in G such that H\cap gQg^{-1}\in {\rm p\!-\!SS}_H.


By employing the Double Coset Counting Formula we have |G|=\sum_a\frac{|H|\ |Q|}{|H\cap aQa^{-1}|}, and since p\nmid [G:Q] then \exists b\in\{a\} such that p\nmid [H:H\cap bQb^{-1}].

But H\cap bQb^{-1}<bQb^{-1} so |H\cap bQb^{-1}|=p^l\ ,\ \exists l\in{\Bbb{N}}, hence, having p\nmid\frac{|H|}{p^l}, this implies that |H|=p^l\alpha, where p\nmid\alpha\ ,\ \exists \alpha\in{\Bbb{N}}.

Then, for H\cap bQb^{-1}<H with |H\cap bQb^{-1}|=p^l we deduce it is {\rm p\!-\!SS}_H



double coset counting formula



Filed under algebra, group theory, math, word algebra

double coset counting formula

the double coset counting formula is a relation inter double cosets HaK, where a\in G and H,K subgroups in G. This is:

\#(HaK)=\frac{|H||K|}{|H\cap aKa^{-1}|}


\#(G/K)=\sum_a[H;H\cap aKa^{-1}]

The proof is easy.

One is to be bounded to the study of the natural map H\times K\stackrel{\phi_a}\to HaK. And it uses the second abstraction lemma.

The formula allows you to see the kinds of subgroups of arbitrary H versus K a p-SS of G, p-SS for the set of the p– Sylow subgroups.

Or, you can see that through the action H\times G/K\to G/K via h\cdot aK=haK you can get:

  • {\rm Orb}_H(aK)=\{haK\} which comply the equi-partition
  • HaK=aK\sqcup haK\sqcup...\sqcup h_taK, so \#(HaK)=m|K|, for some m\in \mathbb{N}
  • {\rm St}_H(aK)=H\cap aKa^{-1}

then you can deduce:

|G|=\sum_a\frac{|H||K|}{|H\cap aKa^{-1}|}

Now, let us use those ideas to prove the next statement:

Let G be a finite group, with cardinal |G|=q_1^{n_1}q_2^{n_2}\cdots q_t^{n_t}, where each q_i are primes with q_1<q_2<...<q_t and n_i positive integers.

Let H be a subgroup of |G| of index [G:H]=q_1.

Then, H is normal.


By employing K=H in the double coset partition, one get the decomposition:

G=HeH\sqcup Ha_1H\sqcup...\sqcup Ha_tH

So by the double coset counting formula you arrive to:

|G/H|=1+[H:H\cap a_1Ha_1^{-1}]+\cdots+[H:H\cap a_tHa_t^{-1}]


q_1=1+\frac{|H|}{|H\cap a_1Ha_1^{-1}|}+\cdots+\frac{|H|}{|H\cap a_tHa_t^{-1}|}

From this, we get \frac{|H|}{|H\cap a_iHa_i^{-1}|}<q_1.

But |G|=q_1|H| as well |H|=|H\cap a_iHa_i^{-1}|[H:H\cap a_iHa_i^{-1}] so

|G|=q_1|H\cap a_iHa_i^{-1}|[H:H\cap a_iHa_i^{-1}], i.e.

[H:H\cap a_iHa_i^{-1}] divides |G|

Then [H:H\cap a_iHa_i^{-1}]=1. So |H|=|H\cap a_iHa_i^{-1}| for each a_i.

This implies H=H\cap a_iHa_i^{-1} and so H=a_iHa_i^{-1} for all the posible a_i, hence, H is normal.



Filed under algebra, categoría, category theory, fiber bundle, group theory, math, math analysis, mathematics, maths, what is math, what is mathematics

fourth Sylow theorem

We are going to reconstruct the salient of a part of the classical theorem:

Each H p-S of G is contained into a Q p-SS of G

Here the reference frame:

1. \#p-SS divides |G|:

The set p-SS must be considered as an orbit of the action G\times p-SS \to p-SS via g\cdot Q=gQg^{-1}.  Since from sylow II we know that each two are conjugated the there is only one orbit

p-SS ={\rm Orb}_G(Q)\leftrightarrow G/{\rm St}_G(Q)

giving us a trivial  orbital partition. Then \#p-SS=|{\rm Orb}_G(Q)|, i.e.

\#p-SS==[G:{\rm St}_G(Q)]=[G:N_G(Q)],

because for the isotropy group is {\rm St}_G(Q)=\{\!x\!\in\!G: xQx^{-1}\!=\!Q\}=N_G(Q)\!\}.

Then |G|=\#{\rm p\!-\!SS}|N(Q)|.

2. Observe also that p\not|#p-SS:

since |G|=p^mr and |G|=|N_G(Q)|[G:N_G(Q)],  as  far as |N_G(Q)|=|Q|[N_G(Q):Q]





which implies that r=[N_G(Q):Q]\cdot\#p-SS, then p\!\!\not|\#p-SS.

Proof of Theorem:

Considering the conjugation sub-action

H\times p-SS\to p-SS,

we get a orbit decomposition p-SS = {\rm Orb}_H(Q_1)\sqcup\cdots\sqcup{\rm Orb}_H(Q_t) with the corresponding class equation

#p-SS = [H:N_H(Q_1)]+\cdots+[H:N_H(Q_t)],

but asumming that |H|=p^{\alpha} then

#p-SS = \frac{p^{\alpha}}{|N_H(Q_1)|}+\cdots+\frac{p^{\alpha}}{|N_H(Q_t)|}.

Now since p\!\!\not|#p-SS then there is some Q_i for which |N_H(Q_i)|=|H|, so


With that, it is easy these: HQ_i<G and Q_i is normal in HQ_i.

Also \pi:H\to HQ_i/Q_i given by x\mapsto\pi(x)=xQ_i  is an epimorphism, so by the fundamental theorem of group-morphisms we have

\frac{HQ_i}{Q_i}\cong\frac{H}{H\cap Q_i},

Observing that H,\ Q_i<HQ_i and |HQ_i|=[H:H\cap Q_i]|Q_i| then

|HQ_i|=\frac{|H||Q_i|}{|H\cap Q_i|}=p^{m+\alpha-\beta},

where |H\cap Q_i|=p^{\beta},

but m is maximal, then \alpha-\beta=0. Hence |H|=|H\cap Q_i| and

H=H\cap Q_i<Q_i.


Confer Milne Chapter 5



Filed under algebra, group theory, math, what is math